The Development of JA33201 Supplementary Course on Pleasant Japanese Language in Order to Develop Japanese Speaking Ability Using The Cooperative Learning TGT Technique with Roleplaying for Grade 12 Students - Jantawongsa, Kanjana; Art-In, Dr.Sitthipon (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2021)
The objectives of the research were 1) To develop JA33201 supplementary course on pleasant Japanese language. 2) To develop Japanese speaking Ability for grade 12 students. 3) To study the satisfaction with learning by supplementary course of the subject JA33201 on pleasant Japanese language. The results of the study were as follows: 1) The results of JA33201 supplementary course on pleasant Japanese language assessment was good criterion. ( = 4.15, S.D. = 0.89) 2) The results of JA33201 supplementary courses The students have speaking skills ability score at an average of 61.71 or 80.80 percent. The total number of students who are successful is 30 students as 100 percent which surpassed the criterion. and 3) The students’ satisfaction reached good criterion ( = 4.19, S.D. = 0.68)